The effect of cyclooxygenase-2 inhibitors on bone mineral density: results from the Canadian Multicentre Osteoporosis Study - Richards, J. B.; Joseph, L.; Schwartzman, K.; Kreiger, N.; Tenenhouse, A.; Goltzman, D. (Osteoporosis international, 2006)
The use of cyclooxygenase-2 (COX-2) inhibitors has been demonstrated to not only impair load-induced bone formation but also prevent menopause-associated bone loss. We hypothesized that COX-2 inhibitor use would be associated with increased bone mineral density (BMD) in postmenopausal women not using estrogen therapy and, conversely, with decreased BMD in men. The Canadian Multicentre Osteoporosis Study is a longitudinal, randomly selected, population-based community cohort. We present data from men (n=2,004) and postmenopausal women age 65 and older (n=2,776) who underwent a BMD measurement and structured interview in the 5th year of the study. The outcome measure was percent difference in BMD (g/cm(2)). Daily COX-2 inhibitor use was reported by 394 subjects. In men, daily use of COX-2 inhibitors was associated with a lower BMD at all hip sites, with a percent difference of -3.1% [95% confidence interval (CI), -6.0, -0.3] between users and nonusers at total hip. In postmenopausal women not using estrogen replacement therapy, daily COX-2 inhibitor use was associated with higher BMD at most sites [percent difference at total hip: +3.0% (95% CI, 0.3, 5.8)]. These effects appeared to be dose-dependent. COX-2 inhibitor use was associated with a lower BMD in men and, on the other hand, with a higher BMD in postmenopausal women not using estrogen replacement therapy. Men who have used COX-2 inhibitors may wish to seek BMD measurement to assess their fracture risk. However, COX-2 inhibitors may have utility in postmenopausal women if bone-selective analogs can be developed.